Computer-based musical interval training program for Cochlear implant users and listeners with no known hearing loss - Bissmeyer, Susan Rebekah Subrahmanyam; Ortiz, Jacqueline Rose; Gan, Helena; Goldsworthy, Raymond Lee (Frontiers in Neuroscience, 2022)
A musical interval is the difference in pitch between two sounds. The way that musical intervals are used in melodies relative to the tonal center of a key can strongly affect the emotion conveyed by the melody. The present study examines musical interval identification in people with no known hearing loss and in cochlear implant users. Pitch resolution varies widely among cochlear implant users with average resolution an order of magnitude worse than in normal hearing. The present study considers the effect of training on musical interval identification and tests for correlations between low-level psychophysics and higher-level musical abilities. The overarching hypothesis is that cochlear implant users are limited in their ability to identify musical intervals both by low-level access to frequency cues for pitch as well as higher-level mapping of the novel encoding of pitch that implants provide. Participants completed a 2-week, online interval identification training. The benchmark tests considered before and after interval identification training were pure tone detection thresholds, pure tone frequency discrimination, fundamental frequency discrimination, tonal and rhythm comparisons, and interval identification. The results indicate strong correlations between measures of pitch resolution with interval identification; however, only a small effect of training on interval identification was observed for the cochlear implant users. Discussion focuses on improving access to pitch cues for cochlear implant users and on improving auditory training for musical intervals.